(untitled) (Revista Innova Educación, 2023)
The psychometric properties of the Cyberbullying Scale for aggressors in Peruvian adolescents were analyzed. This research has a non-experimental, quantitative, cross-sectional approach and instrumental design, in which 1019 adolescents of both sexes, students of public educational institutions of Secondary Level, aged between 12 to 17 years old (M=14; SD=1.56) participated. Results of the confirmatory factor analysis were χ2 = 103.725, p = 0.000, CFI = 0.965, TLI = 0.951 and RMSEA = 0.064. Likewise, convergent validity is reported, showing a moderate correlation between cyberbullying and cyberaggression (r= 0.548; p= 0.00) and an Omega Coefficient = 0.94. In conclusion, the scale consists of 8 items that measure cyberbullying caused by aggressors in an educational environment, whether face-to-face or virtual.